The anaesthetics of architecture - Leach, Neil (MIT Press, 1999)
In this short, intentionally polemical book, Neil Leach draws on the ideas of philosophers and cultural theorists such as Walter Benjamin and Jean Baudrillard to develop a novel and highly incisive critique of the consequences of the growing preoccupation with images and image-making in contemporary architectural culture. The problem with this preoccupation, Leach argues, is that it can induce a sort of numbness as the saturation of images floods the senses and obscures deeper concerns. In this culture of aesthetic consumption, this "culture of the cocktail," meaningful discourse gives way to strategies of seduction, and architectural design is reduced to the superficial play of empty, seductive forms